STUDI KRITIS TERHADAP JURUSAN ATAU PROGRAM STUDI PSIKOLOGI ISLAM - Ahmad Saifuddin (Psikis : Jurnal Psikologi Islami, 2018)
Psychology is a science that studies about soul or psychiatric, mental processes, and personality through behavior and a series of other scientific methods. As a science that studies human behavior in a broad context, psychology has many branches and paradigms. On the other hand, the increasing psychological problems make research and psychology evolve rapidly. The impact of the rapid development of psychology is the emergence of Islamic psychology. Initially, Islamic psychology considers itself as a madhhab. However, nowaday Islamic psychology tries to reinforce its identity. One of them is by establishing the department of Islamic Psychology according to Regulation of the Minister of Religious Affairs No. 33 of 2016. This article tries to discuss about psychology and Islamic psychology, both scientific and college majors, which then is ended with a discussion about Islamic psychology ambiguity as a major. The used method is literature review and interview. The result shows that a lot of less precise points (occurred) on the establishment of Islamic Psychology majors; so that the Islamic psychology as a major needs to be reviewed.